Family expenditures supporting children across income and urbanicity strata. (November 2016) - Coley, Rebekah Levine; Sims, Jacqueline; Votruba-Drzal, Elizabeth
Abstract: Recent decades have seen growth in the level, geographic distribution, and repercussions of income inequality, with unequal access to enriching resources hypothesized to support the intergenerational transmission of inequality. Yet little evidence delineates economic or contextual variation in resources directed at children. Using data from the Consumer Expenditure Survey on 31, 842 families, this study assessed how family expenditures vary across income and urbanicity strata. Results found that high income families spent proportionally more of their total budget on child resources and proportionately less on basic needs compared to lower income families. These patterns buttress arguments that access to enriching resources may be an important mechanism through which economic advantage is passed on to the next generation. Results further found that income disparities in expenditures were heightened in large urban areas and tempered in rural areas. Together results highlight both income and urbanicity disparities in families' expenditures on child-promotive resources. Highlights: High income families spend proportionally more than low income families on child resources. High income families spend proportionally less than low income families on basic needs. Income disparities in spending are larger in urban than rural areas. Higher cost of living may constrain expenditure choices in urban areas.